The Impact of Anemia on Work Productivity Among Tailors: A Quantitative and Qualitative Analysis - Ismawati, Riska Moissan (Institute of Accounting Research and Novation (IARN), 2024)
This research investigates the relationship between anemia and work productivity among tailors, focusing on how this prevalent condition impacts their work performance and productivity. Anemia, characterized by low hemoglobin levels, is known to affect various aspects of health, but its specific implications for occupational productivity, particularly in the tailoring profession, have not been extensively studied. The study employed a mixed-methods approach, combining quantitative data from a sample of 300 tailors with qualitative interviews to assess productivity levels and anemia severity. Quantitative analysis revealed that tailors with anemia experienced a significant reduction in productivity, with severe anemia associated with nearly a 50% decrease in work output compared to non-anemic workers. Qualitative insights highlighted common issues such as fatigue and diminished work capacity among anemic tailors, further substantiating the quantitative findings. The results also identified significant differences based on gender and age, with female and older tailors showing greater productivity losses. These findings indicate that anemia’s impact is not uniform across all demographics, suggesting the need for targeted interventions. The study’s implications are far-reaching, informing health policy by emphasizing the need for improved nutritional programs, routine anemia screening, and better access to healthcare services. It also highlights the necessity for supportive workplace practices and tailored interventions specific to the tailoring profession.